System monitoring intensity of glaze-clear ice generation on wires of overhead transmission lines - V. I. Panteleev; А. V. Maleev (Омский научный вестник)
Improving the reliability and efficiency of power supplying by reducing accidents in electrical networks caused by intense ice and wind loads is an important comprehensive task. The solution of this problem consists of several mainly stages: timely detection of the onset of ice formation, impact on the device for removing ice and frost deposits and efficiency of removing of ice monitoring. This article discusses a system for detecting ice formation based on a fundamentally new technique using the technology of «machine vision». The developed system of ice formation makes identify the thickness of ice wall and indirectly, by the angle of deviation of the wire relative to the horizontal position, to determine the mass of ice deposits and wire sag. Considered monitoring system is located on support in close proximity from the wire and consists of the following mainly elements: an electronic unit, an optical sensor, a solar panel and GSM antenna.